Circumstances of child deaths in Mali and Uganda: a community-based confidential enquiry. Issue 6 (June 2018) - Willcox, Merlin L; Kumbakumba, Elias; Diallo, Drissa; Mubangizi, Vincent; Kirabira, Peter; Nakaggwa, Florence; Mutahunga, Birungi; Diakité, Chiaka; Dembélé, Eugene; Traoré, Mamadou; Daou, Pierre; Bamba, Drissa; et al.
Summary: Background: Interventions to reduce child deaths in Africa have often underachieved, causing the Millennium Development Goal targets to be missed. We assessed whether a community enquiry into the circumstances of death could improve intervention effectiveness by identifying local avoidable factors and explaining implementation failures. Methods: Deaths of children younger than 5 years were ascertained by community informants in two districts in Mali (762 deaths) and three districts in Uganda (442 deaths) in 2011–15. Deaths were investigated by interviewing parents and health workers. Investigation findings were reviewed by apanel of local health-care workers and community representatives, who formulated recommendations to address avoidable factors and, subsequently, oversaw their implementation. Findings: At least one avoidable factor was identified in 97% (95% CI 96–98, 737 of 756) of deaths in children younger than 5 years in Mali and 95% (93–97, 389 of 409) in Uganda. Suboptimal newborn care was a factor in 76% (146 of 194) of neonatal deaths in Mali and 64% (134 of 194) in Uganda. The most frequent avoidable factor in postneonatal deaths was inadequate child protection (mainly child neglect) in Uganda (29%, 63 of 215) and malnutrition in Mali (22%, 124 of 562). 84% (618 of 736 in Mali, 328 of 391 in Uganda) of families had consulted a health-care provider for the fatal illness, but the quality of care was often inadequate. Even in official primary care clinics, danger signs were often missed (43% of cases in Mali [135 of 396], 39% in Uganda [30 of 78]), essential treatment was not given (39% in Mali [154 of 396], 35% in Uganda [27 of 78]), and patients who were seriously ill were not referred to a hospital in time (51% in Mali [202 of 396], 45% in Uganda [35 of 78]). Local recommendations focused on quality of care in health-care facilities and on community issues influencing treatment-seeking behaviour. Interpretation: Local investigation and review of circumstances of death of children in sub-Saharan Africa is likely to lead to more effective interventions than simple consideration of the biomedical causes of death. This approach discerned local public health priorities and implementable solutions to address the avoidable factors identified. Funding: European Union's 7th Framework Programme for research and technological development.